Using interactive collaborative media to improve skills of mathematics teachers to educate students with special needs during covid-19 pandemic - Marwa El-ahwal (International Journal of Instructional Technology and Educational Studies)
Using interactive collaborative media has demonstrated a significant improvement in the performance of the students participating in the experimental group concerning skills of mathematics teachers to educate students with special needs during covid-19 pandemic. Therefore, the would-be teachers have to be more creative and depend on innovative curricula for an effective learning; the thing which necessitates improving mathematics teachers skills. Experimental group included 30 participants whereas controlling group included 30 participants as well. After checking the similarity of the two groups and accepting variables, participants were chosen randomly. The practical method and quasi-experimental design were also used in the study. Results demonstrated differences with statistical significance of the skills of the experimental group: encouraging interaction and collaboration with colleagues and families, encouraging default interaction, designing mathematics lessons according to the comprehensive design for fairness and accessibility, educating mathematical concepts and skills, using technological teaching strategies and evaluating students